Decision support system for the application of the MAUT method in determining the best chat application with roc weighting / Mesran Mesran, Nola Dita Puspa and Dito Putro Utomo - Mesran, Mesran; Dita Puspa, Nola; Utomo, Dito Putro (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
A chat application is a software that is used by someone as a communication tool for two or more people by sending messages, calls, and video calls using an internet network. At this time the development of communication technology in the field of chat applications has developed practically not only sending messages but also being able to send voice messages (voice notes), images (images), video and video calls. Therefore, the many chat application features that are currently scattered make a person confused, especially for beginners in choosing or determining which chat application is the best and most interesting to use. From the problems above, we need a system that can help and recommend someone in selecting or determining the best chat application using the Decision Support System (SPK). it can be stated that the acquisition of the highest preference value has 2 alternatives, namely alternative A1 WhatsApp with a value of 0.31228 and A4 Bbm with a value of 0.31228.